2005
DOI: 10.1097/01.ico.0000159737.68048.97
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Corneal Endothelial Cell Images From a Noncontact Specular Microscope and a Scanning Confocal Microscope

Abstract: The ConfoScan 3 can be used interchangeably with the Robo when the Corners method is used to assess ECD and the magnification of both microscopes is calibrated with an external scale. If the proprietary software provided with the ConfoScan 3 is used, it should be manually corrected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
3
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 20 publications
(20 reference statements)
3
56
3
1
Order By: Relevance
“…In the current study, the potential effect of magnification on ECD was accounted for by the NAVIS software, which contains an internal calibration for magnification. 14 CCT measurement in this study (529 mm) was slightly less than that reported by Sanchis-Gimeno et al 30 (554 ± 16 mm), who studied the corneal thickness of 1000 young (range 20-30 years) emmetropic subjects using a similar Orbscan II slit-scanning corneal topography system. Comparison of CCT with other published reports is limited due to differences in measurement technique.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…In the current study, the potential effect of magnification on ECD was accounted for by the NAVIS software, which contains an internal calibration for magnification. 14 CCT measurement in this study (529 mm) was slightly less than that reported by Sanchis-Gimeno et al 30 (554 ± 16 mm), who studied the corneal thickness of 1000 young (range 20-30 years) emmetropic subjects using a similar Orbscan II slit-scanning corneal topography system. Comparison of CCT with other published reports is limited due to differences in measurement technique.…”
Section: Discussioncontrasting
confidence: 64%
“…5,9,16,17,26,27 With regards to the reliability and repeatability of the NAVIS endothelial analysis system, automated endothelial analysis often fails to correctly identify endothelial cell borders. 14,28 However, Kitzman et al 14 have demonstrated that after manual correction of cell borders detected by the NAVIS automated software, the endothelial density, coefficient of variation of cell area, and percentage of hexagonal cells were not different from those determined by the Corners method. They therefore concluded that if the ConfoScan and its proprietary programme are used to determine cell density, investigators must manually correct cell boundaries on the images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Klais et al 27 compared corneal endothelial cell counts in 42 normal eyes obtained by confocal and specular microscopy and found measurements to be comparable with both methods. Similarly, Kitzmann et al 28 showed that endothelial cell density measured from the images recorded by confocal and specular microscopy were not significantly different from each other when the same programme was used for the measurement.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26] Such agreement for ECD values was, however, obtained on relatively normal appearing endothelia with high ECD values and did require manual correction of erroneous cell boundaries created by the automated method. 24,25 The main purpose of this study was to evaluate the agreement of three endothelial analysis methods used on endothelial images obtained with the Confoscan 4 scanning-slit confocal microscope after corneal transplantation. The reliability of ECD estimates for relatively normal and for very abnormal-appearing endothelia was also evaluated.…”
Section: Introductionmentioning
confidence: 99%